Laparoscopic versus open pancreaticoduodenectomy: a systematic review and meta-analysis of randomized controlled trials - Nickel, Felix; Haney, Caelán Max; Kowalewski, Karl-Friedrich; Probst, Pascal; Limen, Eldridge Frederick; Kalkum, Eva; Diener, Markus K.; Strobel, Oliver; Müller, Beat P.; Hackert, Thilo (Annals of surgery, 2020)
Objective: - To compare perioperative outcomes of laparoscopic pancreaticoduodenectomy (LPD) to open pancreaticoduodenectomy (OPD) using evidence from randomized controlled trials (RCTs). - Background: - LPD is used more commonly, but this surge is mostly based on observational data. - Methods: - We searched CENTRAL, Medline and Web of Science for RCTs comparing minimally invasive to OPD for adults with benign or malignant disease requiring elective pancreaticoduodenectomy. Main outcomes were 90-day mortality, Clavien-Dindo ≥3 complications, and length of hospital stay (LOS). Secondary outcomes were postoperative pancreatic fistula (POPF), delayed gastric emptying (DGE), postpancreatectomy hemorrhage (PPH), bile leak, blood loss, reoperation, readmission, oncologic outcomes (R0-resection, lymph nodes harvested), and operative times. Data were pooled as odds ratio (OR) or mean difference (MD) with a random-effects model. Risk of bias was assessed using the Cochrane Tool and the GRADE approach (Prospero registration ID: CRD42019120363). - Results: - Three RCTs with a total of 224 patients were included. Meta-analysis showed there were no significant differences regarding 90-day mortality, Clavien-Dindo ≥3 complications, LOS, POPF, DGE, PPH, bile leak, reoperation, readmission, or oncologic outcomes between LPD and OPD. Operative times were significantly longer for LPD {MD [95% confidence interval (CI)] 95.44 minutes (24.06-166.81 minutes)}, whereas blood loss was lower for LPD [MD (CI) −150.99 mL (−168.54 to −133.44 mL)]. Certainty of evidence was moderate to very low. - Conclusions: - At current level of evidence, LPD shows no advantage over OPD. Limitations include high risk of bias and moderate to very low certainty of evidence. Further studies should focus on patient safety during LPD learning curves and the potential role of robotic surgery.